Peningkatan Kapasitas Dan Kapabilitas Pengurus Dan Anggota Pokdarwis Srikandi Kelurahan Tinjomoyo Semarang Melalui Bimbingan Teknis - R Basiya; Nungki Pradita; Artin Bayu Mukti (Jurnal Pengabdian Masyarakat Nusantara, 2023)
The role of Pokdarwis in carrying out the development of an area is considered strategic in building an equal distribution of welfare for local communities. Pokdarwis Srikandi, which is based in the Tinjomoyo sub-district area of Semarang, is expected to be able to develop the potential of its area into tourism business activities that can revive the economy of the people in the area. With the average management and members having different educational backgrounds, the Pokdarwis management must work hard to continue to equip and improve the abilities of their members, especially in governance management, because they are the spearheads of the Pokdarwis in providing services to visiting guests or tourists. The form of governance management Technical guidance activities include lectures on Pokdarwis governance, with material related to Pokdarwis administrative governance provided. The next implementation of capacity and capability improvement is the implementation of financial administration training carried out by creating simple financial reports and directly practicing the process of recording the organization's income and expenditure transactions. Governance management capabilities are needed to realize the sustainability of tourism management in the Tinjomoyo Village area, especially in administrative management and financial administration management.